Does land marketization improve eco-efficiency? Evidence from China - Yu, Yantuan; Luo, Nengsheng (Technological and Economic Development of Economy, 2023)
The trend of market-oriented land transaction scheme and the optimal allocation of land resources have become two important components of ecological sustainable development. However, the relevance of analyzing effects of land marketization on ecological and environmental development cannot be overemphasized. The ecological and environmental effects of land marketization are the focus of this paper. We begin by developing a theoretical framework to investigate how land marketization affects eco-efficiency. Moreover, we develop a data envelopment analysis model to measure eco-efficiency. We empirically investigate the effect of land marketization on eco-efficiency using a data set of 251 cities in China over the period of 2003 to 2018. Both theoretical and empirical results show that the land marketization exerts positive effects on eco-efficiency. Specifically, a 100% increase in land marketization level leads to a 2.4 percent increase in eco-efficiency. The heterogeneous effects and spatial effects of the land marketization on eco-efficiency are also examined. Besides, the endogeneity issues are also discussed using instrumental variable approach. Finally, the mechanism analysis shows that land marketization improves eco-efficiency primarily through improving efficiency change, best practice change and technology gap change, respectively. The main conclusions are confirmed by several robustness checks.First published online 30 January 2023